2003
DOI: 10.1074/jbc.m301201200
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Protein 3BP2 Is a Potential Ligand of Src Homology 2 and 3 Domains of Lyn Protein-tyrosine Kinase

Abstract: Adaptor protein 3BP2 was originally isolated as a proteintyrosine kinase c-Abl-Src homology 3 (SH3) 1 domain-binding protein of unknown function (1). 3BP2 was also identified as a Syk kinase-interacting protein by the yeast two-hybrid screening (2). Transient overexpression of 3BP2 resulted in a transcriptional activation of nuclear factor of activated T cell and activator protein 1, which is induced by T-cell receptor aggregation. Ser 225 and Ser 277 of 3BP2 were identified as essential sites for interacting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(91 citation statements)
references
References 39 publications
1
87
0
3
Order By: Relevance
“…Cross-linking of FcRI by Ag triggers a series of protein phosphorylation reactions, phosphorylation of FcRI by Lyn, followed by the phosphorylation of Syk, Btk, and phospholipase C (22)(23)(24) (26 -28). Thus, we examined whether flotillin-1 affects phosphorylation of the MAPK cascade.…”
Section: Effects Of the Expression Level Of Flotillin-1 On Ca 2ϩ Mobimentioning
confidence: 99%
“…Cross-linking of FcRI by Ag triggers a series of protein phosphorylation reactions, phosphorylation of FcRI by Lyn, followed by the phosphorylation of Syk, Btk, and phospholipase C (22)(23)(24) (26 -28). Thus, we examined whether flotillin-1 affects phosphorylation of the MAPK cascade.…”
Section: Effects Of the Expression Level Of Flotillin-1 On Ca 2ϩ Mobimentioning
confidence: 99%
“…Recently, it has been reported that the chaperone protein 14-3-3 interacts with the proline-rich domains of 3BP2 and negatively regulates 3BP2 adaptor function in lymphocytes (3). In addition, 3BP2 binds to the SH2 and SH3 domains of the protein tyrosine kinase Lyn during Fc⑀RI-mediated signaling in mast cells (4). Besides mast cells, 3BP2 also has a key regulatory role in NK cells.…”
mentioning
confidence: 99%
“…Ce domaine paraît indispensable, car sa délétion réduit la capacité de 3BP2 à augmenter l'activité de facteurs nucléaires comme NFAT dans les cellules T et B [4,6]. Le domaine riche en proline, qui s'étend entre les domaines PH et SH2 sur plus de 200 acides aminés, contient de multiples motifs PxxP représentant des sites de fixation pour des protéines à domaine SH3, parmi lesquelles Abl [3], Vav [6], Fyn [4] et Lyn [7]. Le criblage de banques de peptides dégénérés par le groupe de Cantley a montré que la séquence de fixation optimale pour le domaine SH2 de 3BP2 se compose des acides aminés phosphoTyr-Glu-Asn (pYEN), un motif retrouvé dans plusieurs molécules de signalisation incluant les récepteurs tyrosine kinases Flt3/Flk2, EpoR, et G-CSFR [8].…”
unclassified
“…L'interaction entre une forme recombinante du domaine SH2 de 3BP2 et un résidu phosphotyrosine du domaine intracytoplasmique du G-CSFR, connu pour lier Grb2 et Shc, a été récemment décrite, mais les conséquences fonctionnelles de cette interaction pour les cellules hématopoïétiques restent inconnues [9]. Le domaine SH2 de 3BP2 peut également se lier au motif YEN présent dans la partie intracytoplasmique de l'adapteur transmembranaire LAT exprimé par les cellules T et NK [4,10] [7,12]. Le résidu phospho-Tyr183 repré-sente un site de fixation du domaine SH2 de Vav1 [11], alors que le résidu phophoTyr446 interagit avec les domaines SH2 de Lyn et Lck [7,12].…”
unclassified
See 1 more Smart Citation